(untitled) (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
This article provides information and suggestions on studying the history of cultural processes during the years of independence, conducting scientific research, studying foreign experience in the field and bringing it into the field of culture and art, and attracting innovations.